Perception of Educational Learning Environment among Undergraduate Nursing Students - Ranjitkar, Uma Devi; Kalikote, Bhagawati; Koirala, Manisa; Pandey, Apsara; Singh, Ajanta (Journal of Nursing Education of Nepal, 2022)
Background: Learning environment have both direct and indirect influence on learning of the students, their engagement in learning and motivation to learn. How teachers interact with students and how students interact with one another affects learning and can be phrased as positive or negative learning environment. This study aimed to find out students’ perception on educational environment of the undergraduate nursing students. Methods: A cross sectional descriptive design was adopted. Maharajgunj Nursing Campus was the study setting. Complete enumerative sampling method was applied. Total sample size was 218 undergraduate nursing students. Structured self-administered questionnaire Dundee Ready Education Environment Measure (DREEM) an international inventory tool was used to collect data. Analysis was done using descriptive statistics such as frequency, mean, and percentage. Results: Most of the respondents were above 20 years (91.7%) of age, female (98.2%), and followed Hindu religion (95%). More than half (54.6%) were studying B.Sc. Nursing, The total mean score of the respondents in Dundee Ready Education Environment Measures was 130.54 + 17.44 with the score ranging from 75 to 186. The mean score on the subscales student’s perception of learning was 32.22+4.987 with the score ranging from 15-48, student’s perception of teachers 28.26+3.93 ranging from 11 to 41, academic self-perception 22.69+3.709 with the score ranging from 13 to 43, perception of learning atmosphere 30.30+5.196 with the score ranging from 11 to 45 and student’s social self perception 17.05+3.735 with the score 8 to 51. Most of the respondents (85.3%) have positive perception towards educational learning environment. Conclusion: The study concludes that most of the respondents have a positive perception on the learning environment as well as a positive perception towards the teachers, followed by a perception of the learning atmosphere as positive.